Nicaragua : Poverty Reduction Strategy Paper; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
Nicaragua's Poverty Reduction Strategy Paper discusses several strategic policies for boosting medium-term economic growth. The role of the private sector as the main engine of growth through the stimulation of investment and exports is underscored. It also emphasizes the objective of broad-based economic growth that promotes employment and rural development. To this end, the authorities intend to improve the investment climate, increase public infrastructure spending, enhance investment in human capital, and strengthen protection of vulnerable groups.